Investigating the effect of of computer-based cognitive rehabilitation on reducing cognitive avoidance in Students with Specific Learning disorder - akram abbariki; kamran Yazdanbakhsh; khodamorad momeni (Ravānshināsī-i Afrād-i Istis̠nāyī, 2019)
Specific learning disorder (SLD) is a neurodevelopmental disorder.Students with SLD have a high level of cognitive problems, resulting in their academic failure.The purpose of this study was to investigate the effect of computer-based cognitive rehabilitation on cognitive avoidance of students with specific learning disorder. This study was semi-experimental with pre-test and post-test.The population included all third grade to sixth female students with learning disorder in city of Kermanshah. A sample size of 28 were selected and divided into control and experimental groups. Research Instruments included The Cognitive avoidance Questionnaire (CAQ) of Sexton and Dugas (2008), the Colorado Learning Difficulties Questionnaire (CLDQ) and the Wechsler Intelligence Scale for children. Captain Log's cognitive rehabilitation program at 12 session of 50- 60 minute twice a week for the study group was developed. For data analysis, covariance analysis with SPSS software was used. Covariance analysis indicated that the effectiveness of computer-based cognitive rehabilitation caused reduction in children's cognitive avoidance (P<0/001), and a computer-based cognitive rehabilitation can be used as a convenient way to help students with learning disorders to reduce their cognitive avoidance. and help students to use more effective strategies to control anxiety levels and reduce distraction and ultimately improve their academic performance.